Contribuições da estratégia de ensino dos multimodos e múltiplas representações para a abordagem do conteúdo de semicondutores no ensino médio - Giehl, Leide Katia (2018)
This work explores the didactic potential of the multi-mode and multiple representations (MMR) as a teaching strategy for the teaching the theme Semiconductors and its applications in technology devices. The teaching strategy is conducted through the construction and application of a didactic workshop composed of four meeting addressing the content of Modern and Contemporary Physics - Semiconductors applied to technology. The MMR teaching strategy aims to provide students with a range of opportunities to construct, refine and deepen scientific knowledge. So that if a student can not understand a concept in relation to a particular representation, another representation may be more effective and engaging. The main goal of this work is to evaluate the potential of the teaching strategy of the MMR for the teaching of Modern and Contemporary Physics. In order to reach this goal, it was investigated how the conceptual evolution of the students takes place under the multirepresentational activities by means of some diagnostic evaluations. In order to find elements that fulfill our objectives, we have opted for the data analysis divided into two parts. First we observe if there is some conceptual evolution of the students about the main physical concepts, and then analyze how this conceptual evolution takes palce during the workshop period. Data analysis was develope using content analysis technique and interpreted under the conceptual change model. The data analysis provided us with indications that there was a conceptual evolution of the students who participated of the workshop, being this evolution the result of the variety of multirepresentational activities that, taked together, contributed to the didatic functions of the MMR.